A review of rolling-type seismic isolation: Historical development and future directions. (15th October 2016) - Harvey, P. Scott; Kelly, Karah C.
Highlights: Rolling-type isolation systems (RISs) protect structures and equipment from earthquakes. A comprehensive review of experimental and theoretical investigations on RISs is provided. High-performance approaches and novel applications of RISs are reviewed. Uncovered topics requiring additional research are highlighted. Abstract: Rolling-type base isolation as a means of earthquake protection is over a century old but has advanced rapidly in recent years due to an increase in research interest. Significant developments in modeling and testing of rolling-type isolators have expanded our understanding and acceptance of this concept. This paper reviews some of the history of rolling-type isolation, as well as recent research activity focused on high-performance approaches and novel applications. Future research topics have also been identified, such as innovations to increase displacement capacity and decrease displacement demands.